Effects of Age, Period and Cohort on the Unemployment of the Workforce in Gran Santiago, Chile 1957-2006 [Efectos de Edad, Periodo y Cohorte Sobre la Desocupación de la Fuerza de Trabajo en el Gran Santiago, Chile 1957-2006] - Rivero-Cantillano, R (Universidad Autonoma del Estado de Mexico, 2019)
The unemployment of the workforce in Gran Santiago has suffered noticeable variations during the twentieth century, however, much remains to be explained about its causes. This paper in-tends to analyze the effects that the demographic change has had on the unemployment of the work force between 1957 and 2006 from a cohort perspective. With that objective, the Intrinsic Estimator Age-Period-Cohort model was developed, developed by Fu (2000) and Yang et al. (2004; 2008). The results indicate that not only the age of the worker or the specific period in-fluence to explain the unemployment rates in Gran Santiago but also the size factor of the cohort is important, a fact that has been little explored. © 2019, Universidad Autonoma del Estado de Mexico. All rights reserved.